Hirudiniasis in Cattle in Mpwapwa District, Dodoma Region of Tanzania - Misheck A. Mulilo; Joyce Siwila; Philbert B. Madoshi; Richard S. Silayo (Case Reports in Veterinary Medicine)
Hirudiniasis is a condition caused by infestation by leeches. Despite the annoyance, clinical signs, and associated lesions caused by leeches in both humans and animals, the extent of the problem in Tanzania is not well elucidated. Individual animals and people become infested when they drink, bath, or walk through contaminated water sources. Leech infestations are more common in rural areas where water is scarce especially during the dry season. In this report, clinical cases of hirudiniasis in twenty-seven (27) cattle in Mpwapwa, Tanzania, are presented. The report further reviews the morphological features of leeches and creates awareness among the affected cattle farmers and the general public. A total of two hundred (200) live cattle were examined; out of these, 27 cattle had live leeches. There were, on average, 3–8 leeches per animal. Affected cattle had wounds on the gums, buccal mucosa, root of the tongue, and under the tongue with copious amounts of blood-stained frothy discharge. Further, the affected animals had respiratory distress and were rolling their tongues. The leeches were manually removed from all the affected cattle, with uneventful recovery. Laboratory examination revealed segmented, dorsal-ventral flattened, cylindrical parasites which had posterior and anterior suckers. The leech infestation was linked to drinking water from a pond which was suspected to be contaminated with “undescribed organisms” as indicated by the farmers. A follow-up was made and revealed no new cases and complete recovery of the affected animals. Hirudiniasis is one of the neglected diseases in humans and livestock and, therefore, requires integrated efforts especially in areas where water is scarce during the dry season. It is anticipated that this case report will stimulate interest and more studies in the subject matter to understand the extent of the problem and document the species and distribution of leeches in Tanzania.